Babad Pasek Kayu Selem Analisis Struktur - Santika Putra, I Putu Yudhi; Suardiana, I Wayan; Sulibra, I Ketut Ngurah (Humanis, 2017)
This study discuses about text of Babad Pasek Kayu Selem because it has its own uniqueness campares with other literatures, that have forma structure and whole narrative. This study has purpose to help building, preserving, and developing traditional literature especially history (babad) in Bali. The theory that used in this study is structural theory by Teeuw that supported by other researches. In analizing, this study used a method that consists of several steps. They are (1)collecting data, (2)data analysis, (3)result presentation. This study found that the structure of Babad Pasek Kayu Selem is revealed both in forma structure and narrative structure with covers the language which based on this study used Kawi Bali language. Meanwhile, from the content covers plot that is straight plot, which in this history consist of situation, generating circumstances, climax, and denoument, incident; there is 8 incident, 12 backrounds of place and 7 backrounds of time, theme that is the origin of Bhujangga exsistence in Tampurhyang with variety limitations and prohibition, character which cover 1 main character, 1 secondary character, and 13 complementary character, and massage that is to remind the generation of Pasek Kayu Selem to the forefathers and where they are from.
Keywords: history, structure, and text.